Kecemasan Algoritmik serta Implikasi terhadap Stres Kerja dan Kepercayaan Diri Profesional pada Karyawan di Era Digital - Rahmat Saleh; Rahmat Hidayat (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Abstract The digital transformation driven by the Fourth Industrial Revolution has given rise to algorithmic management, where artificial intelligence-based systems actively supervise, evaluate, and direct employees. This new paradigm creates unique psychological challenges known as algorithmic anxiety. This study aims to analyze the influence of algorithmic anxiety on work stress and professional self-confidence among employees in the digital era. This research uses a quantitative approach with a causal associative design. The participants consisted of 250 employees in the city of Padang who work for companies implementing algorithmic management, with an age range of 18 to 35 years, selected through a convenience sampling technique. Data were collected using the Algorithmic Anxiety Scale (SKA), an adaptation of the Perceived Stress Scale (PSS-10), and an adaptation of the Rosenberg Self-Esteem Scale (RSES). Data analysis was performed using a simple linear regression test. The research findings indicate that algorithmic anxiety has a significant influence on work stress and professional self-confidence. This influence is positive for work stress, meaning an increase in algorithmic anxiety will increase work stress. Conversely, the influence is negative for professional self-confidence, where an increase in algorithmic anxiety will decrease the level of professional self-confidence. The contribution of algorithmic anxiety to the dependent variables is 8.8%. In conclusion, algorithmic management is a significant source of psychological pressure for employees in the modern workplace.